Table_5_Transcriptomic Profiling of the Adaptive and Innate Immune Responses of Atlantic Salmon to Renibacterium salmoninarum Infection.XLSX - Khalil Eslamloo; Albert Caballero-Solares; Sabrina M. Inkpen; Mohamed Emam; Surendra Kumar; Camila Bouniot; Ruben Avendaño-Herrera; Eva Jakob; Matthew L. Rise (2020)
Bacterial Kidney Disease (BKD), which is caused by a Gram-positive, intracellular bacterial pathogen (Renibacterium salmoninarum), affects salmonids including Atlantic salmon (Salmo salar). However, the transcriptome response of Atlantic salmon to BKD remained unknown before the current study. We used a 44K salmonid microarray platform to characterise the global gene expression response of Atlantic salmon to BKD. Fish (~54 g) were injected with a dose of R. salmoninarum (H-2 strain, 2 × 10 8 CFU per fish) or sterile medium (control), and then head kidney samples were collected at 13 days post-infection/injection (dpi). Firstly, infection levels of individuals were determined through quantifying the R. salmoninarum level by RNA-based TaqMan qPCR assays. Thereafter, based on the qPCR results for infection level, fish (n = 5) that showed no (control), higher (H-BKD), or lower (L-BKD) infection level at 13 dpi were subjected to microarray analyses. We identified 6,766 and 7,729 differentially expressed probes in the H-BKD and L-BKD groups, respectively. There were 357 probes responsive to the infection level (H-BKD vs. L-BKD). Several adaptive and innate immune processes were dysregulated in R. salmoninarum-infected Atlantic salmon. Adaptive immune pathways associated with lymphocyte differentiation and activation (e.g., lymphocyte chemotaxis, T-cell activation, and immunoglobulin secretion), as well as antigen-presenting cell functions, were shown to be differentially regulated in response to BKD. The infection level-responsive transcripts were related to several mechanisms such as the JAK-STAT signalling pathway, B-cell differentiation and interleukin-1 responses. Sixty-five microarray-identified transcripts were subjected to qPCR validation, and they showed the same fold-change direction as microarray results. The qPCR-validated transcripts studied herein play putative roles in various immune processes including pathogen recognition (e.g., tlr5), antibacterial activity (e.g., hamp and camp), regulation of immune ...